Top corrosion behavior of X65 wet gas pipeline in Yanchang Gasfield - Qixin LIU; Zhenlin LI (You-qi chuyun, 2020)
In order to clarify the top corrosion mechanism of X65 wet gas pipeline in Yanchang Gasfield and to improve thecorrosion protection effect of the pipeline, the coupon comparison test was carried out using a self-made tube top corrosionsimulation test device with high temperature and high pressure, and the variation of corrosion rate of bottom and topcoupons with the time and the morphology characteristics of the surface and cross-section of corrosion coupons were studiedby means of scanning electron microscope. The results indicate that the uniform corrosion rate at the bottom of pipelinedecreases with time, but that on the top has no obvious variation. The uniform corrosion rate at the bottom and on the topvaries greatly, close to 100%. The bottom corrosion is pitted and the corrosion pits tend to connect as a whole. However, obvious local corrosion can be observed on the top, and the top corrosion spots are greater than the bottom corrosion pits.The corrosion product film at the bottom is thick and distributed uniformly, generally having good protective effect to thecoupons. But the corrosion product film on the top is thin and distributed unevenly. No accumulation of corrosion productappears around the top corrosion, and the local corrosion expands rapidly. Most of the top corrosion is localized, with agreater threat to the safe operation of wet gas pipeline.